Peningkatan Pemahaman Tentang Fiqih Ibadah Di Majelis Taklim At-Taqwa Dusun Lestari Jaya Sangatta Selatan - Mahfud Ifendi; Imron Ghozali; Mirnawati Mirnawati; Dewi Sinta; Herlina Herlina; Sulaiman Sulaiman; Suryadi Suryadi (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The study of fiqh is indeed a very vital material. Because this is related to how Islamic law is carried out. Especially about the worship of mahdhah, therefore every Muslim is obliged to learn to understand it so that at the level of implementation it can run well by religious orders. This service activity was carried out at the At-Taqwa taklim assembly in the hamlet of Lestari Jaya which was the location of the KKL of STAI Sangatta East Kutai students related to strengthening and mentoring religious fiqh. In its implementation, of course, there is planning, implementation, and evaluation that must be considered in compiling and implementing a program. The result of this activity is an increase in the knowledge of the members of the taklim assembly related to ablution, obligatory bathing, and prayer. The enthusiasm of the assisted participants also showed a positive attitude so in this activity it is necessary to follow up with similar activities by discussing other topics.